Immunology Guides Skeletal Muscle Regeneration - Sass, F. Andrea (Int J Mol Sci, 2018)
Soft tissue trauma of skeletal muscle is one of the most common side effects in surgery. Muscle injuries are not only caused by accident-related injuries but can also be of an iatrogenic nature as they occur during surgical interventions when the anatomical region of interest is exposed. If the extent of trauma surpasses the intrinsic regenerative capacities, signs of fatty degeneration and formation of fibrotic scar tissue can occur, and, consequentially, muscle function deteriorates or is diminished. Despite research efforts to investigate the physiological healing cascade following trauma, our understanding of the early onset of healing and how it potentially determines success or failure is still only fragmentary. This review focuses on the initial physiological pathways following skeletal muscle trauma in comparison to bone and tendon trauma and what conclusions can be drawn from new scientific insights for the development of novel therapeutic strategies. Strategies to support regeneration of muscle tissue after injury are scarce, even though muscle trauma has a high incidence. Based on tissue specific differences, possible clinical treatment options such as local immune-modulatory and cell therapeutic approaches are suggested that aim to support the endogenous regenerative potential of injured muscle tissues.